Formation of Students' Socio-Cultural and Lingual Competence at Foreign Language Lessons in Primary School - Tetyana Blyznyuk (Vasyl Stefanyk Precarpathian National University, 2016)
The article identifies the problem of formation of socio-cultural and lingual competence of primary school students at foreign language lessons (namely English). The author analyzed the concept of "socio-cultural" and "lingual" competence and their theoretical-methodical components. The essence of the socio-cultural competence is highlighted through internationalization of all aspects of social life and its importance for socialization of modern students and their preparation for intercultural communication. The researcher considered elements of verbal and non verbal communicative behavior of students. The paper presented ways and means of attracting students to get acquainted with the culture of the countries whose language they study. The methodological bases of the usage of the country and language skills and knowledge are actualized by using a particular content.